Positive direct contact between males and females in the sandf and the reduction of gender bias: the importance of self-disclosure, empathy and perspective taking. - Goosen, Jeslyn C. (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.